The Commitment of the Ministry of Environment and Forestry in Supporting Sustainable Development Goal 12 through the Zero Waste Zero Emission Policy in 2020–2024 - Zaharani Firdaushi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
This study examines the commitment of the Ministry of Environment and Forestry in supporting Sustainable Development Goal (SDG) 12 through the Zero Waste Zero Emission (ZWZE) policy during 2020–2024. Using a descriptive qualitative approach, the research analyzes official documents, implementation reports, and secondary data to identify the gaps between formal policy targets and their real-world implementation. The findings reveal that KLHK has established ambitious targets, including reducing waste generation by 30%, mandatory waste sorting at the source, transforming landfills into sanitary facilities, applying circular economy principles, and reducing greenhouse gas emissions in the waste sector. However, the implementation data from 2022–2023 indicates significant discrepancies, such as 65.83% of waste still being landfilled, low household waste sorting (<20%), and uneven deployment of innovative waste processing facilities such as waste-to-energy plants (PLTSa), refuse-derived fuel (RDF), biodigesters, and maggot cultivation. These gaps highlight the importance of active citizen participation, institutional effectiveness, and the integration of ecological principles, which can be analyzed through Andrew Dobson’s Green Politics framework. The study concludes that achieving SDG 12 requires not only formal policy commitments but also operational strategies, cross-sectoral coordination, and enhanced public awareness. The research provides empirical evidence and strategic recommendations to strengthen the implementation of ZWZE and accelerate the achievement of SDG 12 in Indonesia.